Systematic investigations on the production of calcium phosphate based inorganic nanoparticles - Mohd Azrie Awang (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Calcium phosphate ceramic is good candidate for bone substitutes due to their chemical and structural similarity to bone structural. High purity calcium phosphate powders have been synthesized through sol-gel technique using calcium nitrate tetrahydrate and phosphoric pentoxide as the precursors for calcium and phosphorus, respectively. The sol-gel prepared calcium phosphate nanoparticle was characterized for its phase purity, chemical homogeneity and bioactivity. FTIR result combined with the X-ray diffraction exhibited single phase of calcium phosphate with carbonate peaks in the FTIR spectrum. Photomicrograph or scanning electron microscopy (SEM) showed that the obtained powder after applying different physical condition of parameters ( temperature , stirring speed and aging time) is composed of calcium phosphate nanoparticles (38-50mm) . The dissolution rate of calcium phosphate nanoparticles was higher than conventional calcium phosphate nanoparticles and closer to biological aoatite due to its nanostructure dimensions.